Cultural Perspective: Effective Implementation of Stunting Management Policy in West Pasaman Regency - Sri Meiyenti; Nursyirwan Effendi; Defriman Djafri; Dodi Devianto (Universitas Andalas, 2023)
Whether or not a policy is effective can be caused by implementing factors. The implementation implementer referred to as the street bureaucracy is the link between the bureaucracy and the community. In such relationships are influenced by the culture of each. This article discusses the implementation of stunting handling in West Pasaman District, West Sumatra Province. The objectives of this article are: describe the implementation of stunting handling policies by implementers and explain the acceptance of targets to the policy implementation program. This article is based on research using qualitative methods with an ethnographic approach. The research data were collected by observation techniques and in-depth interviews. The results showed that the implementation of stunting prevention in West Pasaman has been formally carried out well. The Regional Apparatus Organization involved and the implementation officer at the spearhead are working seriously with each of their duties. This has made the Regional Government of West Pasaman Regency ranked first in the Convergence Action to Accelerate Stunting Reduction 4 times in a row from 2019 to 2022. However, people in Nagari who are the locus of stunting feel that the program approach actually makes the target community (especially those with stunting children) feel depressed and intimidated, causing resistance to posyandu activities. So it can be said that the implementation of stunting prevention carried out is less effective. This has made the Regional Government of West Pasaman Regency ranked first in the Convergence Action to Accelerate Stunting Reduction 4 times in a row from 2019 to 2022. However, people in Nagari who are the locus of stunting feel that the program approach actually makes the target community (especially those with stunting children) feel depressed and intimidated, causing resistance to posyandu activities. So it can be said that the implementation of stunting prevention carried out is less effective. This has made the Regional Government of West Pasaman Regency ranked first in the Convergence Action to Accelerate Stunting Reduction 4 times in a row from 2019 to 2022. However, people in Nagari who are the locus of stunting feel that the program approach actually makes the target community (especially those with stunting children) feel depressed and intimidated, causing resistance to posyandu activities. So it can be said that the implementation of stunting prevention carried out is less effective.